STATUS KEPEMILIKAN HAK CIPTA ARSITEKTUR YANG DIBUAT BERDASARKAN HUBUNGAN KERJA (SUATU PENELITIAN DI KOTA MEDAN) - YASIR ARFAN (PREMISE LAW JURNAL, 2013)
ABSTRACT Architecture is one of the rights protected in accordance with the provision of Law No.19/2002 on Copyright (known as UUHC). So far, the protection for architecture copyright has not implemented as expected. When a creation of architecture is made in a working relationship, in practice, who has the right of its ownership becomes unclear. In an architecture issue, it is hard to determine who has the right to be called the creator or copyright owner. The result of this study showed that, in Indonesia, without being registered, the copyright keeps being protected. The architects working for a company based on a working relationship are suggested to start to maximally utilize the architecture copyright given by the Law on Copyright to them. Both parties are suggested to always include the clause of architecture copyright ownership in the work agreement the made. Keywords: Status, Ownership, Copyright, Architecture